1999
DOI: 10.1016/s0091-6749(99)70005-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental interaction in allergy and asthma☆☆☆

Abstract: Asthma is an inflammatory disorder of the airways involving coordinate up-regulation of T(H)2-type cytokines encoded in a cluster on chromosome 5q(31-33) on T cells and inflammatory cells. There is also a requirement for local airway susceptibility factors that, together with T(H)2 polarization, results in hyperresponsiveness, variable airflow obstruction, and, over time, remodeling of the airway wall. Asthma has strong genetic and environmental components that interact both in the induction and subsequent exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(99 citation statements)
references
References 59 publications
(63 reference statements)
1
92
0
6
Order By: Relevance
“…We also observed that individual responses to SHS and DEPs are correlated across the endpoints measured in this study. Our results provide further evidence that the severity of common allergic airway diseases, such as allergic rhinitis and asthma, is a consequence of the interplay between common genetic variants and environmental exposures (9,(35)(36)(37). The correlated responses to different exposures suggest that some individuals are at higher risk than others for…”
Section: Discussionsupporting
confidence: 53%
“…We also observed that individual responses to SHS and DEPs are correlated across the endpoints measured in this study. Our results provide further evidence that the severity of common allergic airway diseases, such as allergic rhinitis and asthma, is a consequence of the interplay between common genetic variants and environmental exposures (9,(35)(36)(37). The correlated responses to different exposures suggest that some individuals are at higher risk than others for…”
Section: Discussionsupporting
confidence: 53%
“…It is worthwhile underlining that the prenatal ETS exposure appeared to have a stronger and signifi cant effect on the occurrence of persistent wheezing than that in the postnatal period. The inverse association between the infant's length at birth and persistent wheezing could indicate that a shorter length of the newborns is a proxy measure of a slower biological maturation of the respiratory tract, which obviously depends on many factors, including among others the induction and maturation of the target lung cell population, as well as their relevant enzyme and detoxication systems [33][34][35][36][37]. Animal studies indicated that both intrauterine and postnatal exposure to air pollutants can lead to impaired lung growth [38].…”
Section: R E V I E W P a P E R S W Jędrychowski Et Almentioning
confidence: 99%
“…It has been suggested that a reactivation of the epithelialmesenchymal trophic unit may exist in asthma (51). We would like to extend this notion by proposing that this trophic unit still exists at birth in the neonate who will develop asthma, suggesting the persistence of immature features of the developing lung.…”
Section: Genes Of the Embryologic Differentiation May Govern Airway Rmentioning
confidence: 85%
“…In asthma, abnormal signaling between the epithelium, in contact with the environment, and the underlying (myo)fibroblasts and dendritic cells may reactivate the epithelial-mesenchymal trophic unit, which is involved in fetal lung development and branching (42,51). There are several features of the developing lung which are present in asthma, and it has been observed that allergen exposure induces the expression of some of the these Katz (39) proposed the concept of the Ôallergic breakthroughÕ.…”
Section: Bronchial Remodeling In Asthmamentioning
confidence: 99%